Whole genomic approach in mutation discovery of infantile spasms patients - Lee, Seungbok; Jang, Sesong; Kim, Jong-Il; Chae, Jong Hee; Kim, Ki Joong; Lim, Byung Chan (Frontiers in Neurology, 2022)
Infantile spasms (IS) are a clinically and genetically heterogeneous group of epilepsy disorders in early infancy. The genetic backgrounds of IS have been gradually unraveled along with the increased application of next-generation sequencing (NGS). However, to date, only selected genomic regions have been sequenced using a targeted approach in most cases of IS, and the genetic etiologies of the majority of patients remain unknown. We conducted a proof-of-concept study using whole-genome sequencing (WGS) for the genetic diagnosis of IS. We included 16 patients with IS for this study, and WGS was applied as a first-tier test for genetic diagnosis. In total, we sequenced the whole genomes of 28 participants, including the genomes of six patients, which were sequenced with those of their parents. Among variants identified, we focused on those located in epilepsy or seizure-associated genes. We used two different methods to call relevant large deletions from WGS results. We found pathogenic or likely pathogenic variants in four patients (25.0%); a de novo variant in HDAC4, compound heterozygous variants in GRM7, and heterozygous variants in CACNA1E and KMT2E. We also selected two more candidate variants in SOX5 and SHROOM4 intronic regions. Although there are currently several difficulties in applying WGS for genetic diagnosis, especially in clinical interpretation of non-coding variants, we believe that developing sequencing technologies would overcome these hurdles in the near future. Considering the vast genetic heterogeneity and the substantial portion of patients with unknown etiologies, further studies using whole genomic approaches are necessary for patients with IS.